2004
DOI: 10.1002/marc.200400423
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Dendritic Functionalization of Cellulose

Abstract: Summary: A series of regioselectively dendronized cellulose derivatives has been prepared by the treatment of cellulose in a N,N‐dimethylacetamide/LiCl solvent system with dendrons possessing isocyanate focal substituents. These new materials were characterized using FT‐IR and 13C NMR spectroscopies, and thermogravimetric analysis; the products were highly soluble in a wide range of organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Little work has been published on using dendrimers (the highly ordered hyperbranched polymers), in nanoparticles preparation [42]. However, it has been shown that dendronized cellulose could be used to prepare CdS QDs [43,44]. In the present work, the use of PEI in the synthesis of metal sulfide nanoparticles using cheap and safe inorganic starting materials was explored.…”
Section: Cds and Zns Nanoparticlesmentioning
confidence: 96%
“…Little work has been published on using dendrimers (the highly ordered hyperbranched polymers), in nanoparticles preparation [42]. However, it has been shown that dendronized cellulose could be used to prepare CdS QDs [43,44]. In the present work, the use of PEI in the synthesis of metal sulfide nanoparticles using cheap and safe inorganic starting materials was explored.…”
Section: Cds and Zns Nanoparticlesmentioning
confidence: 96%
“…For example, they exhibit significantly low intrinsic viscosities in solution because of their globular shapes, which is particularly valuable for composite processing. Hassan and coworkers regioselectively dendronized cellulose with diverse siloxy and carbamate dendrons with different peripheral groups by homogenous substitution reactions (Hassan et al 2005;Hassan et al 2004;Hwang et al 2006). The dendronized celluloses possess a wide range of solubilities in organic solvents.…”
Section: Introductionmentioning
confidence: 97%
“…Very recently, dendronized cellulose derivatives were described by Newkome and coworkers for the first time. [5,6] Aminotriester-based…”
Section: Introductionmentioning
confidence: 99%